علمِ حدیث میں ڈاکٹر ضیاءالرحمٰن الاعظمی کی خدماتContributions of Dr. Zia-ur-Rehman al-Āzmī in Ḥadīth Studies (Al-Qamar, 2022)
Dr. Zia-ur-Rehman Azmi who after acquiring knowledge devoted his entire life to the propagation of religion and performed the duty of service to religion in various ways. Being busy though did not give you much opportunity to work in the practical field of da'wah and preaching But from a scientific and theoretical point of view, the authoritative work that you have done is by no means of less importance. Explaining and inviting his followers is a special theme of some of his writings. To fulfill the purpose of this da'wah, he wrote many books in Arabic, Urdu and Hindi language. We will do our best.
Keywords: Dr. Zia-ur-Rehman Āzmī; Ḥadīth; contributions